The public administration dictionary - Chandler, Ralph C.; Plano, Jack C. (New York : Wiley, 1982)
First, entries have been carefully selected for inclusion based on the major foci of the field. Second, the book utilizes a subject-matter chapter format by which key concepts are grouped for study and review purposes.
Includes index.
Includes bibliographical references: p. 383-385.
ne 09/09/2021
Ref.
Keywords: Public administration